The open universe : an argument for indeterminism - Popper, Karl R (Routledge, 2000)
The Open Universe is the centerpiece of the argument of the Postscript. Popper argues in simple language for the freedom, creativity, and rationality of mankind.
Keywords: filozofie; humanitní vědy a umění; Philosophy